Teaching English at Indonesian Islamic Higher Education: An Epistemological Perspective - Irwansyah, Dedi (Dinamika Ilmu: Jurnal Pendidikan, 2018)
English Language Teaching (ELT) practices are strongly underpinned by an epistemological view. Different beliefs on what constitute as sources of knowledge and methods of knowledge acquisition bring about different instructional implications. The case is true within the context of ELT at Indonesian Islamic higher education where the desired goals of the English teaching are not only for mastering language skills and pedagogy but also for strengthening Islamic faith and nurturing virtuous action. This research, therefore, aims to provide a description of how the decision makers and ELT practitioners at the Islamic higher education view the Islamic epistemology conceptually and practically. It addresses an attitude toward the epistemological contestation between Islam and West, as well as the strategies of integrating Islamic epistemology into English language instruction. A case study with a qualitative technique of data collection was conducted. Four decision makers, with a formal educational background of Islamic epistemology, and three ELT practitioners were involved as the research participants. The findings show that: First, ELT has its roots in Quranic revelation and prophetic tradition. Second, the Islamic epistemology and the Western epistemology ought to be interconnected rather than to be put within a contestation framework. Third, the Islamic epistemology should be integrated, explicitly or implicitly, into the curriculum, teaching materials, classroom scenario, assessment, academic atmosphere, and research policy. It is recommended that ELT practitioners responsibly explore the notion of Qur'an as the basis of linguistics and language pedagogy, and creatively accommodate the issues of locality and particularity into their instructional activities.